Prevalence of intellectual disability: A meta-analysis of population-based studies - Maulik, Pallab K.; Mascarenhas, Maya N.; Mathers, Colin D.; Dua, Tarun; Saxena, Shekhar (Research in developmental disabilities, 2011)
▶ The prevalence of intellectual disability across the world is around 1%. ▶ The prevalence is almost two times more in low and middle income countries compared to high income countries. ▶ Highest prevalence was seen in child and adolescent population. ▶ Using standardized diagnostic instruments and disability measurements leads to lower estimates compared to simple psychological assessment tools even if confirmed by clinicians. Intellectual disability is an extremely stigmatizing condition and involves utilization of large public health resources, but most data about its burden is based on studies conducted in developed countries. The aim of this meta-analysis was to collate data from published literature and estimate the prevalence of intellectual disability across all such studies. The review includes studies published between 1980 and 2009, and includes data from populations that provided an overall estimate of the prevalence of intellectual disability. Meta-analysis was done using random effects to account for heterogeneity. Sub-group analyses were also done. The prevalence of intellectual disability across all 52 studies included in the meta-analysis was 10.37/1000 population. The estimates varied according to income group of the country of origin, the age-group of the study population, and study design. The highest rates were seen in countries from low- and middle income countries. Studies based on identification of cases by using psychological assessments or scales showed higher prevalence compared to those using standard diagnostic systems and disability instruments. Prevalence was higher among studies based on children/adolescents, compared to those on adults. Higher prevalence in low and middle income group countries is of concern given the limitations in available resources in such countries to manage intellectual disability. The importance of using standardized diagnostic systems to correctly estimate the burden is underlined. The public health and research implications of this meta-analysis have been discussed.